An investigation into the changes in price momentum after share ex-dividend dates - Marais, Wynand (Department of Finance and Tax, 2016)
This paper examines changes in share price momentum by comparing the share price momentum before and after the ex-dividend date. The study was conducted using price data from shares comprising the Johannesburg Stock Exchange (JSE) Shareholder Weighted Top 40 Index on 30 June 2015. Share price momentum changes were considered over 10 business days, 21 business days and 90 business days before and after the ex-dividend date. The results of the study are as follows: The share price momentum tends to be positive before and after the ex-dividend date. On average, the share price momentum is positive more frequently before the ex-dividend date than afterwards. Comparing before and after ex-dividend date share price momentum, there was no statistically significant difference over 10 and 21 business days. When comparing before and after ex-dividend date share price momentum over 90 business days, a statistically significant difference exists. The reasons for the respective statistically significant and non-significant differences are speculative and are not addressed in this paper. These occurrences could be investigated as further areas of research.